Spinal Schwannomatosis Mimicking Metastatic Extramedullary Spinal Tumor - Idris Nurdillah; Iqbal Hussain Rizuana; Sharis Osman Syazarina (Diagnostics, 2023)
Intradural extramedullary (IDEM) tumors are the most commonly observed intraspinal tumors, comprising over 60% of tumors found within the spinal canal, and the vast majority of these lesions are benign lesions. IDEM metastases are rare, but if they occur, they commonly manifest as leptomeningeal disease, secondary to drop lesions from intracranial metastases from adenocarcinomas of the lung, prostate cancer, breast cancer, melanoma, or rarely, as a result of lymphomas. The purely non-neurogenic origin of IDEM metastases is rare. Herein, we describe a patient with a previous history of treated colon cancer who presented with a progressive neurological deficit and whose imaging revealed multiple intradural, extramedullary and osseous lesions at the cervical and thoracolumbar spines. With the previous known primary and multiplicity of the lesions, an initial diagnosis of spinal metastasis was made, But it was proven to be schwannoma on histology. We emphasize the diagnostic dilemma in this case and the importance of detecting subtle imaging findings, which may be helpful to differentiate between metastatic disease and a second primary tumor.